TINGKAT PEMANFAATAN DAN ESTIMASI POTENSI IKAN CAKALANG (Katsuwonus pelamis) DI KAWASAN TELUK BONE - Jamal, Muhammad; Hasrun, Hasrun; Ernaningsih, Ernaningsih (Hasanuddin University, 2014)
Information about potency and utilization of Skipjack Tuna in Bone Bay region will support regionalmanagement of fisheries resources in Indonesiabased on characteristic and carrying capacity of marine waters,espcially in Bay region. The aims of this study were to estimate potency of Skipjack Tuna and the level of theirutilization in Bone Bay region and to estimate the primary productivity produced by euphotic zone (Pp).Analysis methods used in this study were catch per unit effort(CPUE) and maximum sustainable yield (MSY),vertically generalized production model (VGPM) which required data of photosynthetically active radiationanddepth of euphotic zone, fish production model by considering energy transfer efficiency among trophic level.This study was conducted for eight months in Luwu Regency.The result of the study showed that the utilization ofthe Skipjack Tunawas bigger than the MSY,.The Ppeu was in the range of 483.3143to 1306.027 mgC m. The Skipjack Tuna biomass estimation was in the range of 97.87 to264.47tonnes Keywords : Skipjack Tuna, utilization, potency, fisheries management, Bone Bay